The Revenue, Education, And Awareness of Tax Payer’s Toward Obedience Of Tax Payer’s On The Territory Of The Directorate General Of Taxes In Central Java - Endang Kartini Panggiarti; Sudati Nur Sarfiah (Basic and Applied Accounting Research Journal, 2021)
Taxes are an important revenue of a country to fund state spending and a source of revenue for the state from the public. People have an obligation to pay taxes on their business or activities by referring to the income or results of products or services. Because the payment of this tax is an obligation, community compliance becomes very important to spur state tax revenues. This research aims to determine tax revenue, education, taxpayer awareness of tax compliance. This research method is quantitative, and uses questionnaires with 188 respondents spread throughout Central Java. Researchers have conducted reliability and validity tests, classical assumption tests, and finally regression tests to test all three research hypotheses. The results of all hypotheses are declared accepted, but only the second hypothesis is statistically significant, namely the level of tax education positively affects the level of taxpayer compliance. While the other hypothesis is that the level of tax revenue has a positive effect on the level of taxpayer compliance and the level of taxpayer awareness has a positive effect on the level of taxpayer compliance, declared acceptable although not significant. The conclusion of this study is that tax education has a very positive influence on people's compliance in tax payments. Therefore, tax education in the future will need to be improved to increase the potential payment of taxes to the state. The contribution of this research is that this study can provide insight that education about taxes is still indispensable to increase the country's tax revenues. These directions are written in the format required for the abstract of the paper for the Seminar Nasional Manajemen, Ekonomi, dan Akuntansi – Universitas Bangka Belitung ke IV (SEMEABB IV/ SEMEABB 2021).